The effect of different indole-3-butyric acid (IBA) concentration, two light regimes of in vitro rooting and acclimatization of in vitro teak (Tectona grandis L.f) plantlets - Ab Shukor, Nor Aini; Goh, Boon Ling; R., Ridzuan (Academic Journals, 2009)
Effects of different indole-3-butyric (IBA) concentrations (0, 0.5, 1.0, 2.0, 3.0 and 5.0 mg/l), two light regimes of in vitro rooting and acclimatization on in vitro teak (Tectona grandis L.f) were investigated. Shoots incubated in the light produced higher mean number of roots (2.0) and mean root length of 15.0 and 4.5 mm when supplemented with low IBA concentrations of 0.5 and 1.0 mg/l, respectively. Conversely, when shoots were incubated in the dark, higher mean number of roots (8.0 and 3.0) and mean root lengths (14.0 and 8.8 mm) were produced when supplemented with higher IBA concentrations of 2.0 and 3.0 mg/l, respectively. IBA was found necessary for root induction and growth in light and dark where 2.0 mg/l was optimum as it recorded high mean number of root (6.0 and 8.0) with mean root lengths of 11.8 and 14.0 mm, respectively. High survival percentage of 80% was recorded for those plantlets raised in “jiffy-7” but survival reduced to 40% when grown in the autoclaved soil after one week.